Chemical bond and microwave dielectric properties of two novel low-εr AGa4O7 (A = Ca, Sr) ceramics. Issue 2 (February 2022) - Ma, Jinyan; Chen, Junqi; Tang, Ying; Li, Jie; Fang, Weishuang; Dai, Yimin; Fang, Liang
Abstract: Two novel low- εr microwave dielectric ceramics AGa4 O7 (A = Ca, Sr; called CGO and SGO, respectively) were analyzed by XRD, SEM, and Raman spectroscopy, showed the monoclinic structure with a C2/c space group. Encouraging microwave dielectric properties (CGO: εr = 9.1, Q × f = 40 600 GHz ( f = 12.4 GHz), and τ f = −86.3 ppm °C −1 ; SGO: εr = 9.2, Q × f = 62 400 GHz ( f = 14.6 GHz), and τ f = −63.4 ppm °C −1 ) are obtained. The PVL chemical bond theory indicated that GaO bonds play a role in affecting the εr and Q × f values. The τf of AGa4 O7 (A = Ca, Sr) had adjusted close to zero (0.93CGO-0.07CaTiO3 : εr = 11.3, Q × f = 31, 043 GHz, and τ f = 3.97 ppm °C −1 ; 0.82SGO-0.18LiCa2 Mg2 V3 O12： εr = 11.8, Q × f = 55, 564 GHz, and τ f = 5.62 ppm °C −1 ).